Creation of Intelligent Technology Based on a Unified Artificial Immune System and the Principles of Homeostasis for the Control and Automation of Complex Oil and Gas Industry Objects - Samigulina, Galina; Samigulina, Zarina; Porubov, Dmitriy (2022 International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2022)
The aim of the study is to develop theoretical foundations for creating an intelligent adaptive technology for complex objects control based on a unified artificial immune system (created on the basis of modified algorithms of artificial immune systems) using the principles of immunological homeostasis for industrial oil and gas processing enterprises, taking into account modern industrial equipment. The scientific significance and main development trends, problems and requirements for the development of such intelligent systems are considered. Information about the creation of the theory of homeostasis is given, types of homeostasis and properties of homeostatic systems are considered. The conditions for the transformation of AIS models for oil and gas industry objects are developed, taking into account modern microprocessor technology. The main stages of the developed technology and the practical value of the results obtained are described. The effectiveness of modified AIS algorithms based on the area of homeostasis was evaluated.